IMPLEMENTASI KEGIATAN SHADAQAH DALAM MEMBENTUK EMPATI - Maria Anggi Setyaning Utomo; Iva Inayatul Ilahiyah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2021)
Shadaqah is a treasure that is expended by expecting a reward from Allah SWT and also one of the worship of Ghoiru Mahdho which aims to form empathy forstudents. Although basically the spirit of empathy in students has been planted from birth, with the development of growth and the factors that influence students, it is necessary to sharpen continuously so that empathy for children is always there for him, among these efforts, of them with shadaqah activities applied theoretically and practically. The focus of the problem in this study is 1. How is the Implementation of Shadaqah Activities in Forming Student Empathy at Tembelang 1 Public Middle School? 2. What are the supporting and inhibiting factors for implementing shadaqah activities informing student empathy at Tembelang 1 Public Middle School? Research in this paper uses a type of qualitative field research, while the approach used in this study is a case study approach, data collection techniques used are observation, interviews, and documentation. The results of the study show: 1. The implementation of shadaqah activities informing student empathy found at Tembelang 1 Junior High School must be carried out 3 times a week. Through this activity that is carried out routinely, the effort of the teacher in approaching students by giving them examples is indirectly the teacher instils empathy in students. So that students become accustomed to charity, in addition, students will become more sensitive to the state of the environment. 2. Supporting factors of shadaqah activities informing student empathy are motivation and cooperation and commitment from the teacher's mother, headmaster, students, guardians of students and all school members as well as motivation from outside the school. The inhibiting factors are the lack of self-awareness of some students and the large number of time-consuming school activities that hinder charity activities